The Relationship Between the Pain Experience and Emotion Regulation in Older Adults. Issue 12 (3rd June 2020) - Ghandehari, Omeed; Gallant, Natasha L; Hadjistavropoulos, Thomas; Williams, Jaime; Clark, David A
Abstract: Objective: To investigate the relationship of emotion regulation strategies (i.e., emotional suppression and reappraisal) with pain catastrophizing, fear of pain, pain intensity, worry, and depression as function of age in samples of older and younger adults. Design: Cross-sectional design using validated questionnaires. Setting: Participants resided in the community. They completed validated measures using online questionnaires. Subjects: Two-hundred fifty-seven older adults and 254 younger adults with chronic pain participated. Methods: Participants completed validated questionnaires of emotion regulation strategies, pain-related functioning and mental health. Results: Emotion regulation varied as a function of age and gender. Among our chronic pain sample, older adult males reported lower use of reappraisal and suppression than younger adult males, while older adult females reported higher use of reappraisal than younger adult females. Emotional suppression was positively related to pain catastrophizing, pain intensity, worry, and depression. Reappraisal was negatively related to depression and worry. Interestingly, age showed a positive relationship with fear of pain, pain catastrophizing, worry, depression, and pain intensity, while gender was related to fear of pain and worry. Finally, emotional reappraisal partially mediated the relationship between the affective dimensions of pain intensity and pain catastrophizing among older adults. Conclusions: Our results indicate that reappraisal strategies are important for older and younger adults with chronic pain, pointing to the necessity of considering these strategies when working clinically with such populations. However, given our findings as well as those in the literature, gender should also be considered.